Synchronous intrathyroidal parathyroid carcinoma and thyroid carcinoma: case report and review of the literature - De Falco, Nadia (BMC Endocr Disord, 2021)
BACKGROUND: Parathyroid carcinoma is a rare endocrine malignancy, rarer when synchronous with a non medullary well differentiated thyroid carcinoma. Parathyroid carcinoma accounts of 0.005% of all malignant tumors and it is responsible for less than 1% of primary hyperparathyroidism. The intrathyroidal localization of a parathyroid gland is not frequent with a reported prevalence of 0.2%. Carcinoma of parathyroids with intrathyroidal localization represents an even rarer finding, reported in only 16 cases described in literature. The rare constellation of synchronous parathyroid and thyroid carcinomas has prompted us to report our experience and perform literature review. CASE PRESENTATION: We herein report a case of a 63-years-old man with multinodular goiter and biochemical diagnosis of hyperparathyroidism. Total thyroidectomy with radio-guide technique using gamma probe after intraoperative sesta-MIBI administration and intraoperative PTH level was performed. The high radiation levels in the posterior thyroid lobe discovered an intrathyroidal parathyroid. Microscopic examination revealed a parathyroid main cell carcinoma at the posterior thyroidal left basal lobe, a classic papillary carcinoma at the same lobe and follicular variant of papillary carcinoma at the thyroidal right lobe. To the best of our knowledge, this is the first case documenting a synchronous multicentric non medullary thyroid carcinomas and intrathyroidal parathyroid carcinoma. CONCLUSIONS: Our experience was reported and literature review underlining challenging difficulties in diagnostic workup and surgical management was carried out.